A 3-Arm Randomized Trial for Achilles Tendinopathy: Eccentric Training, Eccentric Training Plus a Dietary Supplement Containing Mucopolysaccharides, or Passive Stretching Plus a Dietary Supplement Containing Mucopolysaccharides - Ramon Balius, MD; Guillermo Álvarez, MD; Fernando Baró, MD; Fernando Jiménez, MD; Carles Pedret, MD; Ester Costa, MS; Daniel Martínez-Puig, PhD (Elsevier, 2016)
Background: Tendinopathy is an overuse tendon injury that occurs in loaded tendons and results in pain and functional impairment. Although many treatments for painful tendons are described, the scientific evidence for most of the conservative and surgical treatments is not always conclusive. Objectives: This study was designed to evaluate the efficacy of 3 different interventions in patients with Achilles tendinopathy. The interventions include the combination of 2 physical therapy programs (eccentric training [EC] or passive stretching [PS]) with a supplement containing mucopolisaccharides. The efficacy of the interventions was evaluated depending on the stage of the disease. Methods: Fifty-nine patients were randomly assigned to 1 of 3 treatment groups, and classified according to the disease stage: reactive versus degenerative tendinopathy. Treatment groups were EC; EC + a dietary supplement containing mucopolisaccharides, type I collagen, and vitamin C (MCVC); and a passive stretching program + MCVC. Patients were evaluated at baseline, 6 weeks, and 12 weeks with the Victorian Institute of Sports Assessment-Achilles questionnaire for function, a visual analog scale for pain, and ultrasound characterization for the evolution of tendon structure. Results: A significant improvement in Victorian Institute of Sports Assessment-Achilles questionnaire score, pain at rest, and pain during activity were detected in all 3 treatment groups at 6 and 12 weeks' follow-up when compared with baseline. In patients with reactive tendinopathy, the reduction in pain at rest was greater in the groups who took the supplemental MCVC than in the EC alone group (P < 0.05). Conclusions: MCVC seems to be therapeutically useful for management of tendinopathies, providing some additional benefit to physical therapy. This is especially evident in early stages of the disease, when the tendon does not present severe matrix and vascular changes. ClinicalTrials.gov identifier: NCT01691716.